sj-pdf-1-eso-10.1177_23969873221148267 – Supplemental material for Age of onset of cerebral venous thrombosis: the BEAST study - Redoy Ranjan; Gie Ken-Dror; Ida Martinelli; Elvira Grandone; Sini Hiltunen; Erik Lindgren; Maurizio Margaglione; Veronique Le Cam Duchez; Aude Bagan Triquenot; Marialuisa Zedde; Michelangelo Mancuso; Ynte M Ruigrok; et al. (SAGE Journals, 2023)
Supplemental material, sj-pdf-1-eso-10.1177_23969873221148267 for Age of onset of cerebral venous thrombosis: the BEAST study by Redoy Ranjan, Gie Ken-Dror, Ida Martinelli, Elvira Grandone, Sini Hiltunen, Erik Lindgren, Maurizio Margaglione, Veronique Le Cam Duchez, Aude Bagan Triquenot, Marialuisa Zedde, Michelangelo Mancuso, Ynte M Ruigrok, Brad Worrall, Jennifer J Majersik, Jukka Putaala, Elena Haapaniemi, Susanna M Zuurbier, Matthijs C Brouwer, Serena M Passamonti, Maria Abbattista, Paolo Bucciarelli, Robin Lemmens, Emanuela Pappalardo, Paolo Costa, Marina Colombi, Diana Aguiar de Sousa, Sofia Rodrigues, Patrícia Canhao, Aleksander Tkach, Rosa Santacroce, Giovanni Favuzzi, Antonio Arauz, Donatella Colaizzo, Kostas Spengos, Amanda Hodge, Reina Ditta, Thang S Han, Alessandro Pezzini, Jonathan M Coutinho, Vincent Thijs, Katarina Jood, Turgut Tatlisumak, José M Ferro and Pankaj Sharma in European Stroke Journal
Keywords: Cardiology; Medicine; 110904 Neurology and Neuromuscular Diseases